Developing preschool children social aptitudes - Ana Teresa Brás; Carlos Sousa Reis (Universidad de Granada, 2012)
The kindergarten teachers must be aware of the importance of the acquisition of social skills for children, with a view to appropriate adaptation and overcoming the various challenges that will have those throughout existence. This article is the presentation of a research work within the pre-school educational context, in the field of ʻSocial and Personal Educationʼ which may lead to improved social skills within the group of children. In order to accomplish this, after the teaching training with the pre-school class which focussed on the acquisition of social competence, an assessment of the modified social skills within the class was carried out. These activities were included in the preschool lesson planning during the ʻSupervised Teaching Practiceʼ. They were developed based on childrenʼs daily life situations, focussing mainly on using games in the learning contexts. The aim of these games was to motivate and involve the children in order to enhance their balanced social development. The results obtained suggest that the introduction of this type of learning activities may be an asset in Pre-school Education because they develop both childrenʼs social skills and social competence. Moreover, this type of learning activities may also lead to changes in childrenʼs social interaction with both adults and their peers which may favour pro social behaviour.